2012
DOI: 10.5505/agri.2012.88700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Blunt And Sharp Needles For Transforaminal Epidural Steroid Injections

Abstract: Özet Amaç SummaryObjectives: The aim of this study was to compare the sharp and blunt needles in order to determine the incidence of complications during transforaminal anterior epidural steroid injections. Methods: In this retrospective study, 185 cases that undergo transforaminal epidural steroid injection with sharp or blunt needles were evaluated between June 2004 and December 2008. Patients age, sex, diagnosis, needle type (sharp or blunt), volume of local anesthetic and steroid injected, complications (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…[8] Blunt needles seem to be more advantageous because when using them, vascular penetration, and paresthesia were less during transforaminal epidural steroid injections. [9] Use of blunt needles also has been suggested by Graham et al . in cervical transforaminal injections.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Blunt needles seem to be more advantageous because when using them, vascular penetration, and paresthesia were less during transforaminal epidural steroid injections. [9] Use of blunt needles also has been suggested by Graham et al . in cervical transforaminal injections.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt tip needles have been shown to reduce the incidence of vascular penetration for transforaminal injections when compared with sharp needles, with an absolute risk reduction of 8.2-11.8% [75,138]. There is also a trend for blunt tip needles to be associated with lower rates of paresthesias, dural puncture and headache, although significance in one study was lacking for these outcomes [75]. No difference in vascular penetration rate has been observed between different types of sharp tip needles [139], obliging practitioners to weigh any perceived advantage of navigation and steering ability against an increased risk of vascular penetration.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Besides paresthesias, uncomfortable sensations may be blunted in patients with spinal stenosis, masking increases in epidural pressure that can injure the spinal cord [137]. Blunt tip needles have been shown to reduce the incidence of vascular penetration for transforaminal injections when compared with sharp needles, with an absolute risk reduction of 8.2-11.8% [75,138]. There is also a trend for blunt tip needles to be associated with lower rates of paresthesias, dural puncture and headache, although significance in one study was lacking for these outcomes [75].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Nahm et al [ 13 ] and Kim et al [ 14 ] reported that the incidence of vascular injection was significantly increased with cervical and sacral level of injections. Özcan et al [ 15 ] reported that using the blunt needles can reduce the intravascular injection and paresthesia during TFESI. Also, animal studies have demonstrated that the blunt needles are less likely than sharp needles to puncture the vital structures including blood vessels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%